The impact of a pharmacist-driven, collaborative practice on diabetes management in an Urban underserved population: a mixed method assessment. Issue 1 (2nd January 2020) - Ray, Sarah; Lokken, James; Whyte, Colleen; Baumann, Amanda; Oldani, Michael
ABSTRACT: The objective of this manuscript is to describe the results of a pharmacist-driven, Type 2 diabetes targeted, collaborative practice within an urban, underserved federally qualified health center. Pharmacists within a primary care team managed patients with chronic illnesses utilizing a collaborative practice agreement. Pharmacists, pharmacy residents, and supervised students provided care for patients with Type 2 diabetes. The first visit incorporated past medical history, medication reconciliation, determination of adherence and patient knowledge of diabetes pathophysiology, care plan, including diet and exercise, medications, and possible complications. Pharmacists had the authority to optimize medications and order laboratory tests and referrals. Diabetes, hypertension, and medication use outcomes data were collected and analyzed to assess the impact of clinical pharmacy services. Patient and provider satisfaction were assessed via surveys and focus group interviews. Ninety-nine patients were included in the evaluation. The mean A1c level was 9.8% at baseline and 8.4% at follow-up ( p < .05). There were significant improvements in patient attainment of A1c <9%, ACE Inhibitor/angiotensin receptor blocker and statin use, and tobacco cessation at follow-up ( p < .05). Eleven providers who responded to the satisfaction survey answered 73% of the questions with strongly agree. The seven patients who participated in the satisfaction survey, and focus group were satisfied with the care they received from the pharmacists. The focus group highlighted similar personal goals, barriers, and interests in nutrition education. Working as part of a collaborative care team, pharmacists were able to have a significant impact on improving the health outcomes of patients with Type 2 diabetes and patient and provider perceptions of the vital role of pharmacists.